Quantitative three-dimensional anatomy of cervical, thoracic and lumbar vertebrae of Chinese Singaporeans - Tan, S. H. (Springer-Verlag, 2003)
This paper details the quantitative three-dimensional anatomy of cervical, thoracic and lumbar vertebrae (C3–T12) of Chinese Singaporean subjects based on 220 vertebrae from 10 cadavers. The purpose of the study was to measure the linear dimensions, angulations and areas of individual vertebra, and to compare the data with similar studies performed on Caucasian specimens. Measurements were taken with the aid of a three-dimensional digitiser. The means and standard errors for linear, angular and area dimensions of the vertebral body, spinal canal, pedicle, and spinous and transverse processes were obtained for each vertebra. Compared to the Caucasian data, all the dimensions were found to be smaller. Of significance were the spinal canal area, and pedicle width and length, which were smaller by 31.7%, 25.7% and 22.1% on average, respectively. A slight divergence, instead of convergence, was found from T8 to T12. According to the findings, the use of a transpedicle screw may not be feasible. The results can also provide more accurate modelling for analysis and design of spinal implants and instrumentations, and also allow more precise clinical diagnosis and management of the spine in Chinese Singaporeans.